Situation Report: Albania, 4 May 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. District Plenum Examines Agricultural Problems / by Louis Zanga Nuclear Accelerator in Albania / by Louis Zanga New Trade Union Chairman / by Louis Zanga Diplomatic Relations with Denmark / by Louis Zanga Expansion of Trade with Austria / by Louis Zanga Awarding Titles and Prizes / by Louis Zanga